Effective learning environment towards learning agility: student’s attitude as mediator / Ainunnazlee Mohd Ali ... [et al.] - Mohd Ali, Ainunnazlee; Mat, Azmi; Kori, Nur Liana; Salleh, Mohammad Zaim; Saiful Bahry, Norliza; Muhamad Yunus, Nor Sara Nadia (Universiti Teknologi MARA Selangor, 2024)
An effective learning environment, characterized by studentcentered teaching methods, access to resources, and a supportive atmosphere, is frequently seen as a catalyst for fostering this agility. The role of students' attitudes, such as motivation, openness to change, and engagement, can significantly impact learning agility among students. This research employs a survey methodology to examine the various elements of a learning environment and their impact on students' agility in learning, focusing on a sample of 323 students from private universities in Selangor. The analysis also explores the extent to which students' attitudes influence this relationship, either enhancing or diminishing the effect of the learning environment on agility. Data collection was conducted via surveys administered to university students, followed by structural equation modeling analysis. The findings indicate that an effective learning environment positively correlates with learning agility, and this relationship is notably enhanced when students demonstrate a positive attitude toward learning. Curiosity, resilience, and a growth mindset are essential elements in optimizing the advantages of an effective learning environment. The study's implications underscore the importance of educators considering student attitudes when creating learning environments intended to cultivate agile, adaptive learners.